2007
DOI: 10.1177/082585970702300104
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Living with Hope Program for Caregivers of Family Members with Advanced Cancer

Abstract: A theory-based intervention, the Living with Hope Program (LWHP), was designed to foster hope in caregivers of family members with advanced cancer. The LWHP was developed from qualitative data and using Harding and Higginson's recommendations for family caregiver interventions as a guide. The LHWP is: a) focused specifically on the caregivers themselves, b) theory based, c) feasible, d) acceptable, and e) pilot tested. The program consists of a hope video and a hope activity titled Stories of the Present. A mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 34 publications
3
56
0
Order By: Relevance
“…Additionally, 31% ( n = 15) of the interventions targeted caregivers of patients with specific cancer diagnoses (i.e., breast (Christensen, 1983; Bultz et al, 2000; Northouse et al, 2005; Badger et al, 2007; Budin et al, 2008; Baucom et al, 2009), prostate (Manne et al, 2004; Campbell et al, 2006; Northouse et al, 2007), brain (Horowitz et al, 1996), hematopoietic stem cell transplantation (HSCT) (Bevans et al, 2010), and lung tumors (Goldberg & Wool, 1985), and pediatric cancers (Sahler et al, 2002; Stehl et al, 2009)). Additionally, 29% ( n = 14) of the interventions specifically targeted ICs of patients who had advanced disease/were receiving palliative care (Walsh & Schmidt, 2003; Cameron et al, 2004; Harding et al, 2004; Hudson et al, 2005, 2008; Keefe et al, 2005; McMillan et al, 2005; Milberg et al, 2005; Northouse et al, 2005; Carter, 2006; Kissane et al, 2006; Duggleby et al, 2007; Walsh et al, 2007; Bowman et al, 2009), whereas the remaining 71% ( n = 35) enrolled ICs of patients who were heterogeneous with regard to their disease stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 31% ( n = 15) of the interventions targeted caregivers of patients with specific cancer diagnoses (i.e., breast (Christensen, 1983; Bultz et al, 2000; Northouse et al, 2005; Badger et al, 2007; Budin et al, 2008; Baucom et al, 2009), prostate (Manne et al, 2004; Campbell et al, 2006; Northouse et al, 2007), brain (Horowitz et al, 1996), hematopoietic stem cell transplantation (HSCT) (Bevans et al, 2010), and lung tumors (Goldberg & Wool, 1985), and pediatric cancers (Sahler et al, 2002; Stehl et al, 2009)). Additionally, 29% ( n = 14) of the interventions specifically targeted ICs of patients who had advanced disease/were receiving palliative care (Walsh & Schmidt, 2003; Cameron et al, 2004; Harding et al, 2004; Hudson et al, 2005, 2008; Keefe et al, 2005; McMillan et al, 2005; Milberg et al, 2005; Northouse et al, 2005; Carter, 2006; Kissane et al, 2006; Duggleby et al, 2007; Walsh et al, 2007; Bowman et al, 2009), whereas the remaining 71% ( n = 35) enrolled ICs of patients who were heterogeneous with regard to their disease stage.…”
Section: Resultsmentioning
confidence: 99%
“…Only one intervention specifically targeted existential concerns of ICs (Duggleby et al, 2007), whereas several others acknowledged the importance of existential issues, including the importance of finding meaning through the cancer caregiving experience (Toseland et al, 1995; Scott et al, 2004; Northouse et al, 2005; Kozachik et al, 2006; McLean et al, 2008). Our group (Applebaum, 2011) has developed a meaning-centered psychotherapy for informal cancer caregivers, designed to enhance meaning and ultimately reduce suffering.…”
Section: Future Directionsmentioning
confidence: 99%
“…16,28,29 Results While in total, 5 interventions described in 24 publications fulfilled the inclusion criteria and were included in this review, many interventions identified during the literature search did not fulfill the inclusion criteria. Exclusions involved not being structured by time and/or content, 30-47 not being focused on palliative care or exclusively focused on bereavement, 48-71 focused on early-stage cancer [72][73] or recurrent breast cancer, 74 not including minor children/parents, [75][76][77][78] or not being evaluated in an empirical study [79][80][81][82][83] (listed regarding first inclusion criterion that did not fit). For reasons and corresponding numbers of exclusions dependent on the stage of the process, see Figure 1.…”
Section: Inclusion Criteria and Assessment Of Study Qualitymentioning
confidence: 99%
“…For instance, a family member or friend can provide sporadic relief from caregiving duties as well as psychological support to both the patient and the caregiver. 7,31 In some studies, caregivers reported feeling reassured when they had a source of support and received assistance, including information and financial, emotional, and practical support. 12 Therefore, healthcare professionals should encourage caregivers to request and receive assistance from family, friends, and formal caregivers.…”
Section: N Discussionmentioning
confidence: 97%